Performance analysis and customer satisfaction of Jamuna Bank Limited Mohakhali Branch - Naim, Rabiul Islam (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.